2014
DOI: 10.1378/chest.14-0681
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Use of Bedside Lung Ultrasound and Echocardiography in Acute Respiratory Failure

Abstract: This study demonstrated for the first time to our knowledge a significantly better performance of TUS than LUS in the diagnosis of ARF. The value of the TUS approach was particularly important to disambiguate cases of hemodynamic pulmonary edema and pneumonia. We suggest that the bedside use of artificial intelligence methods in this setting could pave the way for the development of new clinically relevant integrative diagnostic models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 35 publications
5
85
0
3
Order By: Relevance
“…In both reviews, the prevalence of acute heart failure was very high at 45%. In contrast, in an intensive care study where pneumonia was more prevalent than cardiogenic pulmonary oedema, the presence of B-lines was neither sensitive nor specific for pulmonary oedema [96].…”
Section: The Interstitial Syndromementioning
confidence: 63%
See 3 more Smart Citations
“…In both reviews, the prevalence of acute heart failure was very high at 45%. In contrast, in an intensive care study where pneumonia was more prevalent than cardiogenic pulmonary oedema, the presence of B-lines was neither sensitive nor specific for pulmonary oedema [96].…”
Section: The Interstitial Syndromementioning
confidence: 63%
“…Sonography increased diagnostic accuracy from 63% to 83%. Finally, BATAILLE et al [96] showed that echocardiography combined with chest ultrasound had superior diagnostic accuracy to chest ultrasound alone (81% versus 63%).…”
Section: Impact On Clinician Decision-making: Diagnostic Thinking Andmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Given the great complexity of patients now treated in the departments of Internal Medicine, often suffering from multiple diseases, an integrated approach with clinical examination and bedside echography is potentially able to quickly dissipate a series of questions that, in the presence of chronic or past diseases, would hardly be dispelled through clinical examination only. 5 Along with these undeniable advantages of a young and exciting procedure, I must also warn against excessive leaps forward. Sometimes one gets the impression that especially younger physicians base their approach almost exclusively on the ultrasound to formulate diagnostic hypotheses and implement the related therapies.…”
mentioning
confidence: 99%